Impact of Change of the Interlocking on the Acceleration of Railway Transport: A Case Study from the Podbrezová Railway Station - Adrián Šperka; Michal Valla; Eva Nedeliaková; Juraj Čamaj (Journal of Advanced Transportation)
Accelerating rail transport is a key factor in improving the quality of passenger and freight transport. The main research question of the article asks whether it is possible to increase the speed due to the change in the interlocking. The main research tool is a comparison of the interval of crossing before and after the reconstruction of the interlocking. As the entire research is carried out on a single-track line at the Podbrezová station, the interval of crossing is the most relevant indicator. An associated goal of the entire research is to point out a possible increase in the carrying out of station tracks and an overall improvement in the working conditions of operational staff (station inspectors and switchmen).